Involvement of ENaC in the development of salt-sensitive hypertension - Pavlov, Tengis S. (Am J Physiol Renal Physiol, 2017)
Salt-sensitive hypertension is associated with renal and vascular dysfunctions, which lead to impaired fluid excretion, increased cardiac output, and total peripheral resistance. It is commonly accepted that increased renal sodium handling and plasma volume expansion are necessary factors for the development of salt-induced hypertension. The epithelial sodium channel (ENaC) is a trimeric ion channel expressed in the distal nephron that plays a critical role in the regulation of sodium reabsorption in both normal and pathological conditions. In this mini-review, we summarize recent studies investigating the role of ENaC in the development of salt-sensitive hypertension. On the basis of experimental data obtained from the Dahl salt-sensitive rats, we and others have demonstrated that abnormal ENaC activation in response to a dietary NaCl load contributes to the development of high blood pressure in this model. The role of different humoral factors, such as the components of the renin-angiotensin-aldosterone system, members of the epidermal growth factors family, arginine vasopressin, and oxidative stress mediating the effects of dietary salt on ENaC are discussed in this review to highlight future research directions and to determine potential molecular targets for drug development.